Analyze the correlation between the geomorphic indices and recent tectonic active of the Lo River fault zone in southwest of Tam Dao range - Liem, Ngo Van; Trinh, Phan Trong; Vinh, Hoang Quang; Huong, Nguyen Van; Quan, Nguyen Cong; Phong, Tran Van; Dat, Nguyen Phuc (Vietnam Journal of Earth Sciences, 2016)
The Lo River Fault Zone in southwest of Tam Dao mountain range is believed to be manifestations of an active normal fault. We evaluated the relative active tectonics using three geomorphic indices: hypsometric curves (HC) or hypsometric integral (HI), mountain front sinuosity (Smf) and stream-length gradient (SL). SL index represents the value in the range of 4 to 1325 (gradient - meter). The higher the value SL focuses primarily on central segment. Smf index have values from 1.10 to 8.07, depending on the calculated basin and can be divided into 3 segments: north, center and south with corresponding average values of 5.57, 1.82 and 5.15, respectively. The HI indices of 28 key basins ranging from 0.039 to 0.398 and the dominantly concave hypsometric curves show a weak activity of recent tectonics, especially the vertical slips. The Lo River Fault in this area can be divided into 3 segments: north and south segments show almost inactive, central segment have expressed of recent active tectonic but also not really clear.ReferencesAllen, C.R., Gillepie, A.R., Han, Y., Sieh, K.E., Zhu, C., 1984. Red River and associated faults, Yunnan province, China: Quaternary geology, slip rates, and seismic hazard, Geological Society of America Bulletin,  686-700, 21 fig.Azor, A., Keller, E.A., Yeats, R.S., 2002. Geomorphic indicators of active fold growth: South Mountain-Oak Ridge anticline, Ventura basin, southern California. Geological Society of America Bulletin 114, 745-753.Chen, Y.C., Sung, Q., Cheng, K.Y., 2003. Along-strike variations of morphotectonic features in the Western Foothills of Taiwan: tectonic implications based on stream gradient and hypsometric analysis. Geomorphology 56, 109-137.Delcaillau, B., Deffontaines, B., Floissac, L., Angelier, J., Deramond, J., Souquet, P., Chu, H.T., Lee, J.F., 1998. Morphotectonic evidence from lateral propagation of an active frontal fold; Pakuashan anticline, foothills of Taiwan. Geomorphology 24, 263-290.Delcaillau, B., Laville, E., Amhrar, M., Namous, M., Dugué, O., Pedoja, K., 2010. Quaternary evolution of the Marrakech High Atlas and morphotectonic evidence of activity along the Tizi N'Test Fault, Morocco. Geomorphology 118, 262-279.El Hamdouni, R., Irigaray, C., Fernández, T., Chacón, J., Keller, E.A., 2008. Assessment of relative active tectonics, southwest border of the Sierra Nevada (southern Spain). Geomorphology 96, 150-173.Font, M., Amorese, D., Lagarde, J.L., 2010. DEM and GIS analysis of the stream gradient index to evaluate effects of tectonics: the Normandy intraplate area (NW France). Geomorphology 119, 172-180.Gardner, T.W., Sasowsky, K.C., Day, R.L., 1990. Automated extraction of geomorphometric properties from digital elevation models. Zeischrift für Geomorphologie Supplemental Band 80, 57-68.Harlin, J.M., 1978. Statistical moments of the hypsometric curve and its density function. Mathematical Geology 10, 59-72.Howard, A.D., 1990. Role of hypsometry and planform in basin hydrologic response. Hydrological Processes 4, 373-385.Huang, X.J., Niemann, J.D., 2006. Modelling the potential impacts of groundwater hydrology on long-term drainage basin evolution. Earth Surface Processes and Landforms 31, 1802-1823.Joshi, P.N,. Maurya, D.M., Chamyal, L.S., 2013. Morphotectonic segmentation and spatial variability of neotectonic activity along the Narmada-Son Fault, Western India: Remote sensing and GIS analysis. Geomorphology 180-181 (2013) 292-306.Keller, E.A., Pinter, N., 2002. Active Tectonics. Earthquakes, Uplift and Landscape. Prentice Hall, New Jersey, 362.Le Duc An, 2003. About the exhumation of metamorphic rocks of Con Voi range. Journal of Sciences of the Earth,No.1, 93-95 (In Vietnamese with English abstract).Le Duc An, Dao Dinh Bac, Uong Dinh Khanh, Vo Thinh, Tran Hang Nga, Ngo Tuan Anh, Nguyen Thi Le Ha, 2004. Geomorphology of Red River Fault Zone and natural hazard.P 459-532. Science and Technics Publishing House, Hanoi (In Vietnamese with English abstract).Le Duc An, Lai, Huy Anh, Vo Thinh, Ngo Tuan Anh, Do Minh Tuan, Tran Hang Nga, 2001. Steps of relief of Convoi Mountain characteristics. Journal of Sciences of the Earth, 23(2), 97-104. (In Vietnamese with English abstract).Leloup, P.H., Arnaud, N., Lacassin, R., Kienast, J.R., Harrison, T.M., Trinh, P.T., Replumaz, A., Tapponnier, P., 2001. New constraints on the structure, thermochronology, and timing of the Ailao Shan-Red River shear zone, SE Asia, Journal of Geophysical Research, B, v. 106, 6683-6732.Leloup, P.H., Chen Wenji, Harrison, T.M., Tapponnier, P., 1994. Timing of shear sense inversion along the Red River fault zone. Int. Workshop on Seismotectonics and Seismic Hazard in South East Asia, Hanoi.Leloup, P.H., Lacasin, Tapponnier, P., Scharer, U., Dalai, Z., Xaohan, L., Zhangshan, Shaocheng, J., Trinh, P.T., 1995. The Ailao Shan -  Red Rive shear zone (Yunnan, China), Tertiary transform boundary of  Indochina. Tectonophysics, v. 251,  pp. 3-84.Leloup, P.H., Lacassin, R., Tapponnier, P., Harrison, T.M., 2001. Comment on “Onset timing of left-lateral movement along the Ailao Shan±Red River Shear Zone: 40Ar/39Ar dating constraint from the Nam Dinh Area, northeastern Vietnam” by Wang et al., 2000. Journal of Asian Earth Sciences 18, 281-292. Journal of Asian Earth Sciences 20, 95-99.Lifton, N. A., Chase, C.G., 1992. Tectonic, climatic and lithologic influences on landscape fractal dimension and hypsometry: implications for landscape evolution in the San Gabriel Mountains, California. Geomorphology 5, 77-114.Luo, W., 1998. Hypsometric analysis with a geographic information system. Computers & Geosciences, Vol. 245, No. 8, 815-821.Luo, W., 2000. Quantifying groundwater- sapping landforms with a hypsometric technique. Journal of Geophysical Research, Vol. 105, No. El, Pages 1685-1694, January 25.Mahmood, S. A., and Gloaguen, R.,  2012. Appraisal of active tectonics in Hindu Kush: Insights from DEM derived geomorphic indices and drainage analysis. Geoscience Frontiers 3(4), 407-428.Moglen, G.E., Bras, R.L., 1995. The effect of spatial heterogeneities on geomorphic expression in a model of basin evolution. Water Resources Research 31, 2613-2623.Ngo Van Liem, 2011. Characteristics of landform evolution in relation to recent geodynamics along the Red River Fault Zone, Doctorate thesis, Institute of Geological Sciences, Hanoi (In Vietnamese with English abstract).Ngo Van Liem, Phan Trong Trinh, Hoang Quang Vinh, 2006. The active faults and the maximum earthquakes of the Red River Fault zone in Lao Cai-Yen Bai area, Journal of Sciences of the Earth, Vol. 28, (2), 110-120 (In Vietnamese with English abstract).Ngo Van Liem, Phan Trong Trinh, Nguyen Van Huong, Nguyen Cong Quan, Tran Van Phong, Nguyen Phuc Dat, 2016. Analyze the correlation between the geomorphic indices and recent tectonic active of the Lo River fault zone in southwest of Tam Dao range. Vietnam Journal of Earth Sciences. Vol. 38, No. 1, 1-13 (In Vietnamese with English abstract).Nguyen Quoc Cuong., Zuchiewicz, W., Tokarski. A. K., 1999. Morphotectonic evidence for right-lateral normal slip in the Red River Fault Zone: insights from the study on Tam Dao fault scarp (Viet Nam), J. Geology, Seri B, 13-14, 57-59.Nguyen Xuan Nam, 2015. Quaternary Geology characteristics, present-day tectonic geomorphology of the Da river valley from HoaBinh to Viet Tri and correlation with geological hazards. Doctorate Thesis. Hanoi University of Mining and Geology (In Vietnamese with English abstract).Ohmori, H., 1993. Changes in the hypsometric curve through mountain building resulting from concurrent tectonics and denudation. Geomorphology 8, 263-277.Pedrera, A., Pérez-Peña, J.V., Galindo-Zaldívar, J., Azañón, J.M., Azor, A., 2009. Testing the sensitivity of geomorphic indices in areas of low-rate active folding (eastern Betic Cordillera, Spain). Geomorphology 105, 218-231.Pérez-Peña, J.V., Azañón, J.M., Azor, A., 2009. CalHypso: An ArcGIS extension to calculate hypsometric curves and their statistical moments. Applications to drainage basin analysis in SE Spain. Computers & Geosciences 35, 1214-1223.Phan Trong Trinh, Hoang Quang Vinh, Leloup Philippe Hervé, Giuliani, G., Vincent Garnier., Tapponnier, P., 2004. Cenozoic deformation, thermodynamic evolution, slip mechanism of Red River shear zone and ruby formation. Science and Technics Publishing House, Hanoi. P5-72 (In Vietnamese with English abstract).Phan Trong Trinh, Ngo Van Liem, Nguyen Van Huong, Hoang Quang Vinh, Bui Van Thom, Bui Thi Thao, Mai Thanh Tan, Nguyen Hoang, 2012. Late Quaternary tectonics and seismotectonics along the Red River fault zone, North Vietnam. Earth-Science Reviews 114, 224-235.Phan Van Quynh, Vo Nang Lac, and Tran Ngoc Nam, 1995. Some features of late Paleozoic-Cenozoic deformation tectonics on the territory of Vietnam and neighboring areas. In: Geology, Mineral Resources and Petroleum of Vietnam. Geological Survey of Vietnam, Hanoi, 171-183 (in Vietnamese with an English abstract).Phung Thi Thu Hang, 2011. Study and comparison recent active tectonics between the Red River and the Dien Bien - Lai Chau Fault Zones base on geomorphic indices. Master thesis. VNU University of Science, Hanoi.Shahzad, F., and Gloaguen, R., 2011. TecDEM: AMATLAB based tool box for tectonic geomorphology, Part 1: Drainage network preprocessing and stream profile analysis. Computers & Geosciences 37, 250-260.Strahler, A.N., 1952. Hypsometric (area-altitude) analysis of erosional topography. Geological Society of America Bulletin 63, 1117-1142.Strahler, A.N., 1957. Quantitative analysis of watershed geomorphology. Transactions of the American Geophysical Union 38, 913-920.Tran Dinh To, 2002. The characterize of  Neotectonics of Red River-Chay River Fault Zone. Doctorate Thesis, Institute of Geological Sciences, Hanoi, (In Vietnamese with English abstract).Tran Dinh To, Duong Chi Cong, Vy Quoc Hai, Matthias Becker, Marina Neuman, 2003. Activity  of Red River fault zone at Tam Dao-Ba Vi derived from GPS data (1994-1996-1998-2000). Journal of Sciences of the Earth, 25(4)PC, 511-515 (In Vietnamese with English abstract).Tran Dinh To, Nguyen Trong Yem, 2001.Amplitude and rate of slip of the Red River Zone in late Cenozoic. Journal of Sciences of the Earth, 23(4), 334-353. (In Vietnamese with English abstract).Tran Ngoc Nam, 1999. Red River Fault zone - focus of the scientific debate. Part II: P-T-t paths and post-metamorphic exhumation, Journal of Sciences of the Earth, No.3, 161-167 (In Vietnamese with English abstract).Tran Ngoc Nam, 2002. Exhumation mechanisms of the Day Nui Con Voi. Journal of Sciences of the Earth, No.3,  286-288 (In Vietnamese with English abstract).Tran Ngoc Nam, Mitsuhiro Toriumi, TetsumaruItaya, 1998. P-T-t paths and post-metamorphic exhumation of the Day Nui Con Voi shear zone in Vietnam. Tectonophysics 290, 299-318.Tran Ngoc Nam., Toriumi, M., Sano, Y., Terada, K., Ta, T.T.,, 2003. 2.9, 2.36, and 1.96 Ga zircons in orthogneiss south of the Red River shear zone in Viet Nam: evidence from SHRIMP U-Pb dating and tectonothermal implications. Journal of Asian Earth Sciences 21, 743-753.Trinh Thi Thuy, 2014. Assessment of modern tectonic activity of the Son La fault zones on the basis of tectonic geomorphology. Master thesis. The University of Science - Vietnam National University, Hanoi (In Vietnamese with English abstract).Wang, P.L., Lo, C.H., Chung, S.L., Lee T.Y., Lan, C.Y., Thang, T.V., 2000. Onset timing of left-lateral movement along the Ailao Shan±Red River Shear Zone: 40Ar/39Ar dating constraint from the Nam Dinh Area, northeastern Vietnam. Journal of Asian Earth Sciences. Volume 18, Issue 3, 1 June 2000, 281-292.Willgoose, G., 1994. A physical explanation for an observed area-slope-elevation relationship for catchments with declining relief. Water Resources Research 30, 151-159.Willgoose, G., Hancock, G., 1998. Revisiting the hypsometric curve as an indicator of form and process in transport-limited catchment. Earth Surface Processes and Landforms 23, 611-623.Zuchiewicz, W., Nguyen Quoc Cuong, Jerzy Zasadni, Nguyen Trong Yem, 2013. Late Cenozoic tectonics of the Red River Fault Zone, Vietnam, in the light of geomorphic studies. Journal of Geodynamics 69, 11-30.